The Influence of Environmental, Social, and Governance (ESG) and Leverage on Efficiency and Profitability in the Automotive Sector Listed on the NYSE: A SEM-PLS Approach - Rabih Katon Dwicahyo; Jerry Heikal (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Here is the proofread passage with corrections applied and technical terms italicised where appropriate, with paragraph form retained: The global automotive industry faces increasing pressure to integrate Environmental, Social, and Governance (ESG) principles while maintaining financial performance; yet the relationship between ESG, leverage, efficiency, and profitability remains inconclusive. This study aims to examine the influence of ESG scores (Environmental, Social, and Governance) and leverage on the efficiency and profitability of automotive companies listed on the New York Stock Exchange (NYSE), with efficiency as a mediating variable. Using a quantitative approach, secondary data from 27 automotive companies (representing 44% of the population) were collected from Yahoo Finance up to Q2 2025 and analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The analysis results indicate that the Environmental score (X1) has a positive and significant effect on Profitability (p = 0.015), while Leverage (X4) has a negative and significant effect on Profitability (p = 0.014). However, the Social and Governance variables show no significant influence on either Efficiency or Profitability. Furthermore, Efficiency does not mediate the relationship between ESG scores and Profitability, confirming a no-mediation (direct only) model. The R² value for Profitability (0.619) indicates that the model explains 61.9% of the variance in profitability performance. These findings suggest that improving environmental initiatives and reducing financial leverage are key factors in enhancing profitability within the automotive sector. Future research may extend this model to other industries or regions to assess the generalisability of ESG–financial performance linkages.